2008
DOI: 10.1016/j.neuroimage.2007.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of brain atrophy in MCI patients, identified via high-dimensional pattern classification, predict subsequent cognitive decline

Abstract: Spatial patterns of brain atrophy in mild cognitive impairment (MCI) and Alzheimer's disease (AD) were measured via methods of computational neuroanatomy. These patterns were spatially complex and involved many brain regions. In addition to the hippocampus and the medial temporal lobe gray matter, a number of other regions displayed significant atrophy, including orbitofrontal and medial-prefrontal grey matter, cingulate (mainly posterior), insula, uncus, and temporal lobe white matter. Approximately 2/3 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

41
361
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 443 publications
(414 citation statements)
references
References 78 publications
41
361
2
3
Order By: Relevance
“…The results of this study, as well as results of related studies (Davatzikos, Fan et al 2006, epub;Fan, Batmanghelich et al 2008;Vemuri, Gunter et al 2008;Kloppel, Stonnington et al 2008, epub), bolster our confidence that the methodology adopted herein can considerably assist in the diagnosis of and differentiation between dementias. Representative cross-sections of effect sizes calculated for CN minus FTD (top), CN minus AD (bottom).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The results of this study, as well as results of related studies (Davatzikos, Fan et al 2006, epub;Fan, Batmanghelich et al 2008;Vemuri, Gunter et al 2008;Kloppel, Stonnington et al 2008, epub), bolster our confidence that the methodology adopted herein can considerably assist in the diagnosis of and differentiation between dementias. Representative cross-sections of effect sizes calculated for CN minus FTD (top), CN minus AD (bottom).…”
Section: Discussionsupporting
confidence: 70%
“…However differential diagnosis between FTD and AD based on structural, rather than functional, scans is a greater challenge. The development of sophisticated high-dimensional image analysis and classification methods in the field of computational neuroanatomy during the past decade can potentially help overcome this challenge (Golland 2002;Lao, Shen et al 2004;Csernansky, Wang et al 2005;Davatzikos, Ruparel et al 2005;Davatzikos, Fan et al 2006, epub;Fan, Batmanghelich et al 2008;Lerch, Pruessner et al 2008;Vemuri, Gunter et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity was on par with clinical diagnostic accuracy: Accuracy of AD that is based on histopathologic verification ranges from 85% to 90% (50-52). Although investigators in some prior studies have reported classification accuracy values ranging from 90% to 100% on the basis of MR imaging measures, they used smaller sample sizes (16,31,(53)(54)(55), included AD groups with more severe impairment (53-55), or did not report fully crossvalidated results (16,31,53,54). Failure to cross-validate results produces an optimis-…”
Section: Discussionmentioning
confidence: 99%
“…Second, predictive modeling at the level of the single subject is key to ultimately provide new neuroimaging markers with diagnostic value. Initially, whole-brain morphometry from structural MRI has been used to train models that can discriminate between healthy controls and patients, such as Alzheimer's disease and frontotemporal dementia (Kloppel et al 2008;Fan et al, 2008a, c;Davatzikos et al 2008), fragile-X syndrome (Hoeft et al 2008), psychosis (Davatzikos et al 2005;Fan et al 2008b), depression (Costafreda et al 2009), psychosis (Sun et al 2009), multiple sclerosis (Weygandt et al 2011) and so on. Advances in functional MRI, and more recently resting-state fMRI, have made it possible to study alterations in functional networks (Fox and Greicius 2010) without behavioral confounds (Bullmore 2012).…”
Section: Introductionmentioning
confidence: 99%